Pharmacokinetics and bioequivalence of sunitinib and Sutent® in Chinese healthy subjects: an open-label, randomized, crossover study - Wang, Yanli; Deng, Qiaohuan; Gao, Zhenyue; Liu, Guangwen; Su, Zhengjie; Zhao, Yicheng; Zhang, Lixiu; Yang, Haimiao (Frontiers in Pharmacology, 2023)
Purpose: The purpose of this study was to examine the pharmacokinetics (PK), bioequivalence and safety of generic sunitinib and its original product Sutent® in healthy Chinese subjects through a phase-I clinical trial. Methods: The study selected two groups of 24 healthy Chinese subjects in a 1:1 ratio through random allocation. Each participant received either 12.5 mg of sunitinib or Sutent® per cycle. A total of 15 different time points were employed for blood sample collection during each cycle. Furthermore, a comprehensive assessment of the drugs' safety was consistently maintained throughout the trial. Results: The average adjusted geometric mean ratios (GMR) (90% CI) for the primary PK parameters Cmax, AUC0-t and AUC0-∞ were 97.04% (93.06%-101.19%), 98.45% (93.27%-103.91%) and 98.22% (93.15%-103.56%), respectively. The adjusted GMRs for essential pharmacokinetic (PK) parameters all met the requirements for bioequivalence, with values within the acceptable range of 80% - 125%. In addition, the two drugs showed comparable results for the other PK parameters. These results indicate that the two drugs were bioequivalent. Furthermore, both drugs showed well safety. Conclusion: The research results proved that the PK and safety profiles of sunitinib in healthy Chinese subjects were comparable to those of Sutent®. These results advocate the clinical application of generic sunitinib as a potential alternative to original product Sutent® in the treatment of certain medical conditions.